From PISA to national branding: exploring Finnish education®. Issue 2 (4th March 2017) - Schatz, Monika; Popovic, Ana; Dervin, Fred
ABSTRACT: Since the recent global paradigm shift in the governance of higher education toward business and marketing, internationally competitive education is increasingly considered as an asset for governments. Consequently, governments started to invest in education branding and marketing their educational systems. In Finland, national interest in education branding rose especially since the country's success in the programme for international student assessment studies created a positive reputation of its basic education. In this article, the authors investigate how this reputation is transformed into a general Finnish education brand, based upon Finland's official Country Brand Report (2010). The governmental discourse on Finnish education reveals a fusion of education and national branding, which is why the authors suggest to discuss the Finnish education brand as Finnish education®. The article provides an analysis of the elements constituting the brand and opens up a critical discussion on the ethics of branding education through cultural and national characteristics.